Intra- and inter-laboratory evaluation of an improved multiplex-PCR method for detection and typing of Salmonella - Martinez-Ballesteros, Ilargi; Paglietti, Bianca; Rementeria, Aitor; Laorden, Lorena; Garcia-Ricobaraza, Maria; Bikandi, Joseba; Rubino, Salvatore; Garaizar, Javier (The Journal of Infection in Developing Countries, 2012)
Introduction: We developed and evaluated a multiplex-PCR method for rapid detection of the most common Salmonella serovars in both developed and developing countries. Additionally, the stability of the premixed reagents at high room temperature was studied. Methodology: Fifty-two Salmonella strains belonging to the collections of the University of Sassari, Italy, and to the University of the Basque Country, Spain, and a collection of a hundred blinded strains, were used to evaluate the multiplex-PCR. Primers targeting genes STY1599 and fliC were selected, and the method was evaluated both intra and inter-laboratories. Results: The inter-laboratory reproducibility was 95.92%, with a kappa index of 0.757 that indicates a substantial agreement and a high accuracy (80.81%). The sensitivity, specificity, accuracy and precision indexes for the Salmonella genus and S. Typhi targets were maximum, although the targets for Paratyphi A, Typhimurium and Enteritidis showed less accuracy. During a seven-week period, hot-start multiplex-PCR runs were performed with reagents mixed with wax to test their stability at 30ºC, and no significant variation in the patterns of amplification was observed. Conclusions: An improved multiplex-PCR for rapid detection of the most common serovars of Salmonella operable in both developed and developing countries has been designed and tested intra and inter-laboratories. Following a careful optimization protocol will not only allow the confirmation of any suspicious colony by the amplification of the Salmonella genus target, but also the preliminary adscription to the prevalent serovars. Premixed reagents with wax facilitate the throughput and stability of reagents at high room temperatures.